Observation of the decay Λb0 → pK−μ+μ− and a search for CP violation - Aaij, R; Adeva, B; Adinolfi, M; Evans, T; Gandini, P; Cazon, BR; Hadavizadeh, T; Harnew, N; Hill, DRF; Jalocha, PG; John, MJJ; Jurik, NP; et al. (Springer, 2017)
A search for CP violation in the decay Λb0 → pK−μ+μ− is presented. This decay is mediated by flavour-changing neutral-current transitions in the Standard Model and is potentially sensitive to new sources of CP violation. The study is based on a data sample of proton-proton collisions recorded with the LHCb experiment, corresponding to an integrated luminosity of 3 fb^−1. The Λb0 → pK−μ+μ− decay is observed for the first time, and two observables that are sensitive to different manifestations of CP violation are measured, ΔACP ≡ ACP(Λ0b→pK−μ+μ−) − ACP(Λ0b→pK−J/ψ) and a aT-odd/CP, where the latter is based on asymmetries in the angle between the μ+μ− and pK− decay planes. These are measured to be ΔACP = (−3.5 ±5.0(stat) ±0.2(syst))×10^−2, aT-odd/CP = (1.2 ±5.0 (stat) ±0.7 (syst))×10^−2,and no evidence for CP violation is found.